Protocol to investigate sensorimotor features in young children with autism using functional and resting-state fMRI data from the NIMH Data Archive - Kristina Denisova; Daniel M. Wolpert (STAR Protocols)
Summary: Head movements cause artifacts in infant neuroimaging that can often render acquired data unusable. Here, we present a protocol that harnesses head motion from fMRI and resting-state (rs)-fMRI NIMH Data Archive (NDA) data to obtain quantitative measures of sensorimotor function in young children and associate them with future cognitive and autism outcomes. We describe steps for downloading, organizing, and pre-processing fMRI data to yield data on in-scan head motion. We then detail procedures for preparing phenotypic data to link with sensorimotor data.For complete details on the use and execution of this protocol, please refer to Denisova and Wolpert.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.